The Evaluation of Cardiac Emergency Management in National Institute of Cardiovascular Diseases Hospital, Dhaka, Bangladesh (Bangladesh Journal of Dental Research & Education, 2013)
Emergency department is one of the most important part of the hospital and also vulnerable to criticism. The reputation of a hospital rests to a large extent on the service of emergency department. The sudden and unexpected nature on the emergency produces panic and psychological disturbances to the relatives, which must be valued and borne in mind during organization and management of services. A descriptive type of cross sectional study was conducted at Emergency Department of National Institute of Cardiovascular Hospital, Dhaka to evaluate the existing facilities, waiting time for the patients for receiving treatment, emergency referral rate and availability of health personnel, overall management and patients suggestion to improve the services of the emergency department. A total of 150 patients were interviewed by a structured questionnaire and a checklist was utilized for equipments and drugs. It was observed that the mean age 49.49 years. About 38.7% patients were attended by doctor within 6-10 minutes. Shifting of the patients form emergency department to another hospital was 12%.  87.3% patients were satisfied with time to complete treatment. In emergency department 69.3%   patients were satisfied with reception facility, 89.3% patients were satisfied with given treatment, 92% patients were satisfied with doctors service and 74% patients were satisfied with the service of the support staff. About 90% patients were satisfied with overall management. The findings of cardiac emergency services obtained through check-list were fairly comparable with the opinions expressed by the patients. For further management of emergency department patients gave suggestion for arrangement of waiting room and toilet facility, X-ray and other laboratory facility for emergency patient should be made available for all the duty shift, drugs should be supply adequately and on regular basis. They suggested for augmentation of the equipments, drugs and security and other facilities and recruitment of some trained service providers. According to the patients the Emergency Department is well-studded to manage most of the cardiac emergencies. However, specific problems identified by different stakeholders need to be critically appraised by the authority to improve the services further.DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16245 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 52-57